Ultrasound Assessment of Lumbar Dural Sac Diameter in Pregnant Patients Compared to Age Matched Non-Pregnant Women - Sharma, Mona; Paudel, Sushil; Dhungel, Saurya; Shrestha, Ujma; Moktan, Sushila Lama (Journal of Nobel Medical College, 2026)
Background: Spinal anesthesia in obstetric practice is a gold standard practice. Pregnancy causes changes in lumbar spine anatomy, including the dimension of the dural sac. However, if pregnancy alone is responsible for these changes or other variables combine to create these changes remains undetermined. This study aims to compare the dural sac diameter in pregnant and their age matched non-pregnant counterparts and its association with other clinical parameters.Materials and Methods: An observational cross-sectional study was conducted in 40 term pregnant and 40 non-pregnant age matched controls. The dural sac diameter at L3-L4 interspace was measured in sitting position in both groups. Reliability was assessed with intraclass correlation coefficient. The difference in mean dural sac diameter was assessed. Stratified Linear regression was used to assess the association between age, body mass index and gestational age and dural sac diameter within each group.Results: The median dural sac diameter was significantly smaller in pregnant patient’s median: 1.12 cm (IQR: 0.20) compared to the non-pregnant group median: 1.31 cm (interquartile range: 0.20) P < 0.001. Ultrasound measurement demonstrated reliability in both groups non-Pregnancypregnant= 0.933(95% CI: 0.888-0.961) and pregnant = 0.874 (95% CI: 0.805-0.929). Age was associated significant decrease in dural sac diameter in non-pregnant group (B=-0.011 cm/year (p =0.033) but non-significant in pregnant group.Conclusion: Dural sac diameter is significantly reduced at late term pregnancy compared to non-pregnant women. Ultrasound provides good reliability for this measurement.